THE INFLUENCE OF THE JIGSAW TYPE COOPERATIVE LEARNING MODEL ON THE LEARNING OUTCOMES OF EIGHTH GRADE STUDENTS IN SOCIAL AT UPTD SMP NEGERI 12 PEMATANGSIANTAR - Vera Elisabet Siahaan; Tumpal Manahara Siahaan; Herlina Hotmadinar Sianipar (RADJA PUBLIKA, 2025)
This study aims to determine the influence of the Jigsaw Type Cooperative Learning Model on student learning outcomes in Social Studies (IPS) for eighth-grade students at UPTD SMP Negeri 12 Pematangsiantar in the 2024/2025 academic year. The research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The sample was selected through purposive sampling: class VIII-4 as the experimental group using the Jigsaw Type Cooperative Learning Model, and class VIII-3 as the control group using the conventional (lecture) method, with 32 students in each class. The research instrument consisted of a multiple-choice test with 25 items, which had been tested for validity, reliability, difficulty level, and discriminating power. The validity test showed that all items were valid (r count > r table = 0.349), with the highest validity coefficient being 0.8019 and the lowest 0.3665. The instrument's reliability was 0.807 > 0.396, indicating that the test was reliable. The normality test indicated that both classes had normally distributed data (X² count < X² table), and the homogeneity test indicated that both groups were homogeneous (F count = 1.025 < F table = 1.804). The results showed that the experimental class had an average score of 80 with a standard deviation of 10.36, while the control class had an average score of 74.25 with a standard deviation of 10.10. The t-test revealed t count = 2.21 > t table = 1.67, indicating a significant difference in learning outcomes between the two classes. Therefore, it can be concluded that the Jigsaw Type Cooperative Learning Model has a significant influence on student learning outcomes in Social Studies and is more effective than the conventional method.